Entrepreneurial alertness of founder-managers and the moderating effect of their fear of failure - Montiel-Campos, Héctor (Serbian Journal of Management, 2022)
The purpose of this paper is to empirically examine entrepreneurial alertness as a process and the influence of fear of failure on this process in the context of small firms. The hypotheses are tested within a sample of 179 founder–managers from small manufacturing firms in Eastern Mexico using a hierarchical regression analysis. The results show that the association and connection dimension partially mediates the relationship between the scanning and search dimension and the evaluation and judgment dimension. Also, these relationships are negatively moderated by fear of failure. This study contributes to the existing opportunity recognition research, specifically to better understand entrepreneurial alertness as a process that simultaneously crosses three different dimensions and incorporates the influence of fear of failure.